Woman using Beckman/SDS Integrated Computer System (1964)
The commercial solid-state computer system included a Beckman 2200 analog computer and Scientific Data Systems 920 digital computer.
Keywords: Analog computers; Scientific apparatus and instruments; Computers; Electronic digital computers; Beckman Instruments, Inc.; Scientific Data Systems